Aberrant expression of claudin‐6 contributes to malignant potentials and drug resistance of cervical adenocarcinoma. Issue 4 (13th February 2022) - Ito, Yui; Takasawa, Akira; Takasawa, Kumi; Murakami, Taro; Akimoto, Taishi; Kyuno, Daisuke; Kawata, Yuka; Shano, Kodai; Kirisawa, Kurara; Ota, Misaki; Aoyama, Tomoyuki; Murata, Masaki; et al.
Abstract: Recent studies have revealed that aberrant expression of tight junction (TJ) proteins is a hallmark of various solid tumors and it is recognized as a useful therapeutic target. Claudin‐6 (CLDN6), a member of the family of TJ transmembrane proteins, is an ideal therapeutic target because it is not expressed in human adult normal tissues. In this study, we found that CLDN6 is highly expressed in uterine cervical adenocarcinoma (ADC) and that high CLDN6 expression was correlated with lymph node metastasis and lymphovascular infiltration and was an independent prognostic factor. Shotgun proteome analysis revealed that cell‐cell adhesion‐related proteins and drug metabolism‐associated proteins (aldo‐keto reductase [AKR] family proteins) were significantly increased in CLDN6‐overexpressing cells. Furthermore, overexpression of CLDN6 enhanced cell‐cell adhesion properties and attenuated sensitivity to anticancer drugs including doxorubicin, daunorubicin, and cisplatin. Taken together, the results indicate that aberrant expression of CLDN6 enhances malignant potentials and drug resistance of cervical ADC, possibly due to increased cell‐cell adhesion properties and drug metabolism. Our findings provide an insight into a new therapeutic strategy, a CLDN6‐targeting therapy, against cervical ADC. Abstract : High claudin‐6 (CLDN6) expression was correlated with lymph node metastasis and lymphovascular infiltration and was an independent prognostic factor of cervical adenocarcinoma. Shotgun proteome analysis revealed that cell‐cell adhesion‐related proteins and drug metabolism‐associated proteins (aldo‐keto reductase [AKR] family proteins) were significantly increased in CLDN6‐overexpressing cells. Furthermore, overexpression of CLDN6 enhanced cell‐cell adhesion properties and attenuated sensitivity to anticancer drugs including doxorubicin, daunorubicin, and cisplatin.